An industrial quality control study on Star Packaging Corporation - Alcantara, Raymund; Carpio, Jenelyn Ann.; Navarro, Julie Anne.; Nicolas, Julius (Diliman, Quezon City College of Engineering, 2004)
The utilization of plastic bottle containers is increasingly becoming an important integral for the production of condiments and mineral water in the market particularly now that the production of such, especially the latter, has become a lucrative business in the market economy. Among those few companies in the Philippines that produce these plastic bottles or more appropriately termed as Polyethylene Terephthalate (PET) bottles is Star Packaging Corporation. The production process of Star Packaging Corporation can generally be classified in two : the Injection Forming Process and the Blow Molding Process, where for each of these, the outputs are preforms and bottles, respectively. The study was conducted with the primary focus on the Injection Forming Process, particularly in Injection Machine 1 of the company. Currently, the company inspects 32 preforms hourly to check the presence of defects in these materials. Occurence of defects in the preforms and in the bottles can lead to classification of what would have been Class A bottles into Class B and Reject bottles. This is avoided as this can lead to a decrease in monetary yield of the company (since Class B bottles and rejects are sold at a minimum price). Exploratory tools such as Pareto Diagram and Ishikawa (Fishbone Diagram)were utilized to determine the top three most occurring problems that must be dealt with immediately for a corrective action. The results showed that Minor Crystallinity, Long Strings, and Minor Scratches accounted for 27.97 percent, 27.41 percent and 23.57 percent of the most occurring defects on preform materials. A c-chart was established to assess this condition and it turned out that the out of control data were found to be due to the variation in the temperature and pressure parameters of the injection machines (for Minor Crystallinity), improper setting up of temperature of the injection machines and unclean cavities (for Long Shots), and improper material handling by operators for minor scratches. The following are recommended to help eliminate or reduce nonconformities: It is recommended that a proper storage area for resins be installed to reduce raw material combination, correct labelling of screws must be used in machine adjustments, an establishment of a machine maintenance schedule, establishment of proper materials handling procedure, an assignment of a default setting when frequent adjustments of machine parameters are encountered, and a stricter inspection procedure conducted by the Quality Control Heads that will have to undergo seminars to learn intensive quality control topics and techniques. It is of utmost importance as well that the company gives focus on the working environment conditions of the employees especially in the Blowing Machines where noise exposure is a great risk for the safety of the workers. A stricter policy on the use of earmuffs must be employed to ensure the safety of the workers. This section can be addressed by applying the philosophies of Methods Engineering.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Star Packaging Corporation; Package goods industry; Quality control